Alimentos: uma temática geradora do conhecimento químico - Pazinato, Maurícius Selvero (2012)
The focus of this paper is the teaching of Chemistry through the theme Food . Therefore we seek to develop teaching methodologies which associated to this theme would promote the learning of the Chemistry contents and would help in the development of the skills and the competences necessary for the exercise of citizenship. Before applying this research, in order to detect how the theme "Food" is presented in high schools, it was analyzed the most used Chemistry textbooks by the teachers from RS up to the year 2011 and one of the five projects approved by the PNLD-2012 in relation to the approach of this theme. We verified that all books analyzed show food in an attempt to contextualize the content of Chemistry and that what distinguishes them is the kind of approach. Moreover, through this analysis, we noted that the series of books approved by the PNLD-2012 contextualizes Chemistry in a substantial way, using various strategies and approaching issues related to the civic education. At the beginning of this research, we had the supposition that the traditional approach of Chemistry do not get good results with regard to student learning and that the use of the theme "Food" matched to differentiated teaching methodologies would help the understanding of the scientific concepts and the civic education. From this, we developed two thematic workshops and prepared a case study, which were applied to a class of third grade of high school in a public school in the town of Santa Maria - RS - Brazil. The data of this study was collected through questionnaires, textual productions, exercises, preparing reports and notes taken by the researcher during the interventions, and analyzed according to the discursive textual analysis. Through the results of this investigation, we concluded that the teaching of Chemistry was favored by the use of the theme "Food" and teaching methodologies based on the role of students. The students felt motivated by the various activities proposed, especially by conducting experimental activities. Thus, the Chemistry was addressed as one of the possible tools to the understanding of daily life, particularly in relation to food and healthy eating.